Resting-State Functional Connectivity in Autism Spectrum Disorders: A Review - Hull, Jocelyn V.; Dokovna, Lisa B.; Jacokes, Zachary J.; Torgerson, Carinna M.; Irimia, Andrei; Van Horn, John Darrell (Frontiers in Psychiatry, 2017)
Ongoing debate exists within the resting state fMRI literature over how intrinsic connectivity is altered in the autistic brain, with reports of general over-connectivity, under-connectivity, and/or a combination of both. Classifying autism using brain connectivity is complicated by the heterogeneous nature of the condition, allowing for the possibility of widely variable connectivity patterns amongst individuals with the disorder. Further differences in reported results may be attributable to the age and sex of participants included, designs of the resting state scan, and to the analysis technique used to evaluate the data. This review systematically examines the resting state fMRI autism literature to date and compares studies in an attempt to draw overall conclusions that are presently challenging. We also propose future direction for rs-fMRI use to categorize individuals with ASD, serve as a possible diagnostic tool, and best utilize data-sharing initiatives.